The Giant Condyloma (Buschke-Löwenstein Tumor) in the Immunocompromised Patient - Atkinson, Andrew L. (Hindawi Publishing Corporation, 2014)
Since Buschke and Löwenstein first described the giant condyloma in 1925 (which subsequently was named Buschke-Löwenstein tumor), there have been scattered reports over the past 90 years describing presentation and different avenues of treatment for patients with this condition. It is well known that immunocompromised individuals are at an increased risk of anogenital disease caused by human papillomavirus (HPV). In this report, we present the management of two HIV positive patients with giant condylomas. Both patients presented with urinary outflow obstruction and sepsis. Though giant condylomas are a rare phenomenon, these two cases underscore the importance of early treatment intervention, especially in the immunocompromised patient.